Harmoniasi Pikiran Tubuh dan Jiwa Melalui Yoga sebagai Gaya Hidup - Made Wirawan; Kadek Hemamalini; Nova Wibawa (Amal Insani Foundation, 2024)
Doing yoga regularly with full discipline will create a balance between mind body and soul for human life. This service process initially targeted 45 participants who were given questionnaires and interviews to determine the level of understanding of the service process, its benefits, and its impact on yoga participants. In general, the participants' understanding was quite good, although the practice of yoga asanas was still an obstacle in the learning process. Most yoga participants stated that this service was beneficial both as individuals and as part of society, especially people in the East Jakarta area. Not only that, there is positive reinforcement that occurs through this service process. On the other hand, the problem of limited meeting time is still an obstacle in improving his yoga practice. Practically, it is hoped that this service can be applied by yoga participants at Pura Aditya Jaya Rawamangun as a center for Hindus in Jakarta, so that doing yoga can be used as a useful lifestyle for Hindus in Jakarta. Apart from that, it is hoped that this service can contribute academically in determining themes of community service, especially those related to the development and socialization of Yoga teachings.